Keys to successful scientific VGI projects - Ingensand, Jens; Composto, Sarah; Ertz, Olivier; Rappo, Daniel; Nappez, Marion; Produit, Timothée; Oberson, Mathias; Widmer, Ivo; Joost, Stéphane (PeerJ Preprints, 2016)
Scientific projects are increasingly using volunteered geographic information (VGI) in order to collect and validate geographic data. This concept relies on the three challenges that first of all users can be found and second be convinced to collaborate and contribute and that scientists finally are able to gather high quality data for their projects. In this paper these three challenges are discussed using the experience with three different research projects: Urbangene, Signalez-nous and BioSentiers.
Keywords: citizen science; Volunteered geographic information (VGI); PPGIS; crowdcrafting; crowdsourcing; data quality